PENGARUH INSTAGRAM SEBAGAI MEDIA ONLINE SHOPPING FASHION TERHADAP PERILAKU KONSUMTIF MAHASISWI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Sofia Miranda; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Instagram as a social media today the function is no longer just a media facilitates its users to present themselves and socialize in cyberspace. Now social media has been used to trading some products to consumers, known as an online shop. Online shop on Instagram now emerging along the fashion updated and the increasing of needs. It can propel consumptive behavior when the individuals affected by exposure to the online shop on Instagram and can not control the excessive craving. This research starts on the Stimulus-Response theory. In this research Online Shop on Instagram is the stimulus provided by the media to the student so that the student response purchasing continuously. This research aimed to find out the influence of Instagram as media of online shopping fashion towards consumptive behavior among the students of Political Science and Social Science Faculty in University of Riau.The method used in this study is a quatitative methode of explanation, data collection techniques in this study using questionnaire. The number of samples for this study were 96 respondents. Sampling using Accidental Sampling. In this study, simple linear regression with SPSS 23 program was used to analyze the data.Based on the result, Instagram as the media of online shopping fashion with indicators (Participation, Openness, Conversation, Community, Interconnecting) influenced consumptive behavior (Impulsive Buying, Prodigality, Irrational Buying) among the students of Political Science and Social Science Faculty in University of Riau. It was obtained that regression coefficient values is Y = 0.998 + 0.341 X 0.000 with a significance level of less than α = 0.05. It means that there is the influence of Instagram as online shopping fashion media towards consumer behavior among students of Political Science and Social Science Faculty in University of Riau was 38.4% and in the category of influential weak, while the remaining 61.6% is influenced by other factors not examined in this research.Keyword : Instagram, Online Shop, and Consumtive Behavior